Influence of Child-Rearing Practices on Sexual Adventurism among Junior High Students in Ghana - Eyiah-Bediako, Sylvia; Omotosho, Joshua Adebisi; Ocansey, Sylvia Kabumle; Kwarteng-Nantwi, Eugene (Journal of Education and Practice, 2025)
Purpose: This study examined the influence of child-rearing practices on sexual adventurism among Junior High students in Ghana. Methodology: The descriptive survey design was adopted for the study. A sample of 525 students were selected from an accessible population of 2,492 for the study. Data was collected with an adapted version of the Youth Sexual Intention Questionnaire (YSI-Q). Descriptive and inferential statistics were used to analyse the gathered data. Findings: The research revealed among others that child-rearing practices significantly predicted sexual adventurism among the target. A high level of sexual adventurism, characterised by marked intentions to engage in sexual activities, with a high efficacy for sexual intimacy were also found among the respondents. Despite reports of fairly weak disciplinary acts employed by parents generally, respondents basically acknowledged the role of consistent parental monitoring with immense parental warmth as important in child up-bringing. Unique Contribution to Theory, Practice and Policy: It was thus recommended that parents adopt stricter disciplinary measures, especially in relation to shaping the sexual attitudes of their children at a tender age. Guidance Coordinators and school counsellors were also encouraged to guide students to channel their sexual energies into useful physical and creative activities, rather than resorting to masturbation to satisfy their strong sexual urges. Conclusions drawn from the study include projecting parental discipline as a useful tool in promoting acceptable behavior among Junior High students, especially regarding sexual adventure.